MANFAAT UBI KAYU DALAM PEMENUHAN KEBUTUHAN HIDUP PETANI HKM WANA LESTARI I, KECAMATAN PLAYEN, KABUPATEN GUNUNGKIDUL - Indah Novita Dewi; Evita Hapsari (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2019)
Dryland farmers in Gunungkidul Regency have been planting cassava as intercropping plants with intercropping systems along with other crops on their land. This model of agroforestry planting was also applied to the HKm land by members of the Wana Lestari I farmer group in Getas Village, Playen Sub-District. Nearly all members of the group planted cassava on HKm land. This article intends to uncover the benefits of cassava for Wana Lestari I farmer, as well as the potential for future development to increase the income of farmer. The study was conducted by survey method with respondents as much as 30% of the population. Respondents who still plant cassava on the plots of land are 80%. Cassava are divided into three benefits, namely as a source of food, as a source of family income, and as a source of animal feed. Potential development of cassava is still very large, and can be done by doing post-harvest processing. It will make the products have added value and then increase the selling value of various processed cassava